The Qiroati Method As An Approach To Introducing Hijaiyah Letters To Early Childhood Children - Riski Yuliana; Maria Qori'ah; Viena Wanidha Andriani; Fitriatul Masruroh; Riris Wahyuningsih; Ria Octa Viana; Abdullah Boraheng (Universitas Negeri Makassar, 2026)
This study aims to examine in depth the implementation of the Qiroati Method in introducing the hijaiyah letters to children aged 5–6 years at Ban IBatu School, Southern Thailand, while identifying various obstacles that arise in the learning process. This study uses a qualitative case study approach. Data collection techniques include non-participant observation, semi-structured interviews with the principal, Qiroati teachers, and class teachers, and documentation. Data were analyzed using Miles and Huberman with the results of the study showing that the implementation of the Qiroati Method was carried out through three main stages, namely planning, implementation, and evaluation which were carried out systematically. The implementation of this method has been proven to develop children's abilities to recognize the hijaiyah letters, pronounce letters according to makhraj, and distinguish letters with similar shapes and sounds. However, during implementation, several obstacles were still encountered, such as limited teacher competence in applying the method, the influence of children's everyday language, and limited learning time. Therefore, the Qiroati Method can be considered effective as an approach to learning the hijaiyah letters in early childhood, especially in the context of minority Muslim communities.